A novel finite element formulation for the buckling analysis of layered composite beam structures - Santos, Hugo A.F.A. (2018)
A novel finite element formulation for the buckling analysis of two-layer composite beam structures will be presented. The beam elements possess a single flexible shear interface and each layer is modelled by means of Timoshenko’s theory. The formulation relies on a hybrid variational principle of complementary energy only involving force/moment-like variables as fundamental unknown fields. The approximate field variables are such that all equilibrium differential equations hold in strong form, and the inter-element equilibrium as well as the Neumann boundary conditions are enforced by means of the Lagrangian-multiplier method. The accuracy and effectiveness of the proposed formulation will be demonstrated through the analysis of several numerical tests.